Bending performance and failure mechanisms of hybrid and regular sandwich composite structures with 3D printed corrugated cores - S.Z.H. Shah (17808635) (2023)
The effect of core geometry and hybridization on the bending performance and failure mechanisms of carbon fibre-reinforced polymer (CFRP) and glass fibre-reinforced polymer (GFRP) corrugated sandwich composite structures (SCS) were experimentally investigated using a three-point bend test. The CFRP and GFRP corrugated cores and facesheets were produced using Fused Filament Fabrication (FFF) and vacuum-assisted infusion processes, respectively. Three types of corrugated SCSs were built: SCSs with different core geometries (circular, square, trapezoidal, sinusoidal, and triangular), hybrid SCSs with different CFRP and GFRP cores and facesheets, and fully 3D-printed CFRP and GFRP SCSs. The corrugated SCS with square core geometry outperformed due to the presence of vertical walls and a large bonding area. The hybrid SCSs with a CFRP core showed a significant load drop due to shear failure in the 3D-printed core caused by weak inter-layer bonding. In contrast, the hybrid SCS with a GFRP core deformed plastically and absorbed more energy without failure due to strong inter-layer bonding. In fully 3D printed SCSs, the GFRP specimen failed catastrophically due to higher bending stress at the bottom facesheet, while the CFRP undergoes plastic deformation without failure. Results elucidate that the hybrid corrugated SCS with a GFRP top facesheet and 3D-printed core is an appropriate configuration for superior bending performance. The proposed 3D-printed SCS enables optimising complex shapes and material distribution in the core, resulting in improved strength-weight ratios. These findings will make an important contribution to the design and development of fibre-reinforced 3D-printed SCS for lightweight and high-performance applications. Other Information Published in: Composite Structures License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.compstruct.2023.117580